Construction and Deconstruction: The Theme of Fleetingness in Poems by Juan Ramón Jiménez, and Pedro Salinas - Andrew P. Debicki (Studies in 20th & 21st Century Literature, 1983)
Both Juan Ramón Jiménez and Salinas reveal in their poems a striving to capture the essences of things, continuing in this quest a tradition coming to them from symbolist poetry. By examining several poems written by them, however, we discover a basic difference in their way of embodying this striving. Juan Ramón, concerned with the perfection of form, remains within a logocentric tradition in which the poem attempts to embody its meanings objectively; Salinas, on the other hand, writes poems the meanings of which evolve with successive readings and reflect the theme of reality's fleetingness. A close analysis of the texts exemplifies this difference and also suggests that in spite of it the poems of both authors remain subject to possible "deconstructions" on the part of the reader.
Keywords: Juan Ramón Jiménez; Salinas; poetry; Spanish poetry; essence; reality; symbolist poetry; logocentric tradition; embodiment; meaning; objectivity; comparison; reader; deconstruction